2019
DOI: 10.1111/acps.13100
|View full text |Cite
|
Sign up to set email alerts
|

Validation of ICD‐11 PTSD and complex PTSD in foster children using the International Trauma Questionnaire

Abstract: ObjectiveICD‐11 introduces post‐traumatic stress disorder (PTSD) and complex PTSD (CPTSD) as two distinct trauma‐related disorders. Using the International Trauma Questionnaire (ITQ) as disorder‐specific measure, this study is the first to examine the factorial and construct validity of ICD‐11 PTSD, CPTSD and the ITQs’ applicability in children.MethodsTwo hundred and eight Austrian foster children completed a set of standardized measures. Excluding participants who reported not having experienced any kind of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
94
5
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(125 citation statements)
references
References 54 publications
19
94
5
7
Order By: Relevance
“…Hyland, Shevlin, Brewin et al, 2017 ). Recent studies in children reported the two-factor higher-order model as best fitting in foster children using the ITQ (Haselgruber et al, 2020b ) and the correlated six-factor model as best fitting in children from the general population using the ITQ-CA (Kazlauskas et al, 2020 ). As foster children have been shown to resemble more a clinical than a non-clinical population (Tarren-Sweeney, 2008 ), results in children seem to corroborate findings in adults, where the two-factor higher-order model was more often identified as best fitting in clinical populations (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hyland, Shevlin, Brewin et al, 2017 ). Recent studies in children reported the two-factor higher-order model as best fitting in foster children using the ITQ (Haselgruber et al, 2020b ) and the correlated six-factor model as best fitting in children from the general population using the ITQ-CA (Kazlauskas et al, 2020 ). As foster children have been shown to resemble more a clinical than a non-clinical population (Tarren-Sweeney, 2008 ), results in children seem to corroborate findings in adults, where the two-factor higher-order model was more often identified as best fitting in clinical populations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The BIC, however, clearly favoured Models 3 and 4, both fitting the data similarly well. This can be explained by the high correlation between PTSD and DSO in Model 4, which may be indicative of PTSD and DSO representing less distinctive factors in children as assessed by the ITQ-CA than by the ITQ (Haselgruber et al, 2020b ; Hyland, Shevlin, Brewin et al, 2017 ). This may be attributable to item formulations or due to age and associated developmental changes, warranting further research using the ITQ-CA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations